Energy-Demanding Redox Transformations via Electrophotocatalysis - Kang, Wen-Jie; Tung, Chen-Ho; Wu, Li-Zhu (Synthesis, 2025)
Electrocatalysis and photocatalysis are two widely recognized approaches to organic synthesis. Over the past decades, these strategies, leveraging distinct energy sources (electricity or light), have demonstrated remarkable capabilities in facilitating chemical transformations. Integrating the broad reactivity of photochemistry with the high chemoselectivity of electrochemistry, the recent advent of electrophotocatalysis (also referred to as photoelectrocatalysis) has garnered increasing attention. This innovative approach is poised to revolutionize organic synthesis by capitalizing on their synergistic benefits. This short review aims to encapsulate the recent advancements in electrophotocatalytic energy-demanding redox transformations. These include, but are not limited to, C–H functionalization, C–X functionalization, and C=X functionalization, highlighting the potential of electrophotocatalysis to enhance the efficiency and selectivity of organic synthesis processes.1 Introduction2 Electrophotocatalytic C–H Functionalization3 Electrophotocatalytic C–X Functionalization4 Electrophotocatalytic C=X Functionalization5 Conclusion
Keywords: photoelectrocatalysis; electrophotocatalysis; functionalization; C–H bond; C–X bond; C=X bond